Association of platelet deficiency with severe retinopathy of prematurity: a review. (10th July 2022) - Seliniotaki, Aikaterini K.; Haidich, Anna‐Bettina; Moutzouri, Stella; Lithoxopoulou, Maria; Ziakas, Nikolaos; Lundgren, Pia; Hellström, Ann; Mataftsi, Asimina
Abstract: Aim: The aim of this review was to compile existing evidence on the role of platelets in the development of severe retinopathy of prematurity (ROP), highlight the strengths and weaknesses of the available studies and critically discuss the reported data. Methods: A comprehensive literature search was conducted on PubMed from January 2000 to January 2022, and the reference lists of the included studies were screened manually. Results: There were 19 primary studies that fulfilled the eligibility criteria. Experimental research indicated lower platelet count in mice oxygen‐induced retinopathy model compared with normoxia controls, while platelet transfusions suppressed neovascularisation. The latter finding was not consistently confirmed in clinical research, where a low platelet count, an increased number of thrombopenic episodes and of platelet transfusions have all been implicated in the development of ROP requiring treatment, either type I or aggressive posterior or both. However, existing studies exhibit significant clinical heterogeneity and present methodological limitations that imperil their reliability and validity. Conclusion: Platelet deficiency has been associated with severe ROP. However, critical thresholds of platelet parameters are still unrecognised. Future research is required to determine whether platelet parameters can be predictive biomarkers for ROP requiring treatment and at what thresholds.